PERANCANGAN UI/UX LEARNING MANAGEMENT SYSTEM (LMS) APLIKASI MOBILE EDU-LEARN MENGGUNAKAN METODE DESIGN THINKING - Muhammad Naufal Ashiddiq (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Distance learning during the Covid-19 pandemic has the potential to reduce student enthusiasm for learning. The problems faced by Learning Management System (LMS) users are the lack of features that support distance learning, many students are left behind in their learning and teachers who find it difficult to control students and the Learning Management System whose features are not yet complete enough. Based on this problem, the Mobile Edu-Learn application was built which provides easy distance learning with features that support teachers in controlling students and reduces the decline in student enthusiasm for learning with features needed by users. This research uses the Design Thinking method which goes through 5 stages : Emphatize, Define, Ideate, Prototype, Testing. The results of this research are a prototype Learning Management System for the Mobile Edu-Learn application by implementing features that have been suggested by users such as integrated features with the Zoom application, downloading student grades, academic reminders (attendance, assignments and tests), and discussion groups. At the testing stage, using two methods, namely task scenarios with maze tools and usability testing, resulted in an average score of 80.83 with a grade scale of B, adjective rating excellent and included in the Acceptable category with two design iterations.